Dynamics of a plant-herbivore model with toxin-induced functional response - Ya Li; Z. Feng (Mathematical Biosciences and Engineering)
Traditional functional responses for plant-herbivore interactions donot take into account explicitly the effect of plant toxin.However, considerable evidence suggests that toxins set upper limitson food intake for many species of herbivorous vertebrates. In thispaper, a mathematical model for plant-herbivore interactionsmediated by toxin-determined functional response is studied. Themodel consists of three ordinary differential equations describingone herbivore population and two plant species with differenttoxicity levels. The effect of plant toxicity on herbivore's intakerate is incorporated explicitly in the model by assuming anincreased handling time. The dynamical behaviors of the model areanalyzed and the results are used to examine the influence oftoxin-determined intake in the community composition of plantspecies. The bifurcation analysis presented in this paper suggeststhat the toxin-mediated functional response may have dramaticeffects on plant-herbivore interactions.